PENGUKURAN PERFORMANSI REFRIGERATOR ALAMI MODEL MOHAMMED BAH ABBA DENGAN MENGGUNAKAN BEBAN AIR - , ADITYA PRADIPTA; , Dr. Eng. M. Kholid Ridwan, S.T., M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This clay refrigerator is an aluminium cylinder placed inside a clay pot. Space between them is filled by sand. To make them cold, the sand is watered until it entered the sand and clay pot. The water will evaporate through the pore of clay pot. Water evaporation absorbs heat from the load inside the aluminium chamber, so that the temperature inside the aluminium chamber will decreased. Two sets of clay refrigerator with different size are tested in a room temperature between 25Â°C â 30Â°C. The temperature difference between control water outside and water inside the refrigerator is measured. The test performed two times. First, testing for 24 hours with refrigerator closed. And second, testing for 24 hours with refrigerator open and close 30 seconds repeatedly every hour. With the refrigerator closed, the small sized refrigerator can decrease the water temperature with average temperature difference with the control water (ÎT) 1.9Â°C, and for the large sized refrigerator ÎT is 2.2Â°C